2006
DOI: 10.1210/en.2005-1012
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemia, But Not Other Factors Associated with Insulin Resistance, Acutely Enhances Colorectal Epithelial Proliferation in Vivo

Abstract: The similarity in risk factors for insulin resistance and colorectal cancer (CRC) led to the hypothesis that markers of insulin resistance, such as elevated circulating levels of insulin, glucose, fatty acids, and triglycerides, are energy sources and growth factors in the development of CRC. The objective was thus to examine the individual and combined effects of these circulating factors on colorectal epithelial proliferation in vivo. Rats were fasted overnight, randomized to six groups, infused iv with insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
94
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 48 publications
5
94
0
Order By: Relevance
“…31 In vivo studies have shown that high insulin levels enhance colorectal and breast cancer cell proliferation via receptors on the tumors. 32,33 Furthermore, treatment with metformin, which lowers insulin levels, decreases the incidence and size of mammary adenocarcinomas in tumor-prone transgenic mice. 34 Human glial tumors possess insulin receptors with binding activities and characteristics identical to peripheral insulin receptors, and insulin has been shown to stimulate glucose uptake in cultures of human GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…31 In vivo studies have shown that high insulin levels enhance colorectal and breast cancer cell proliferation via receptors on the tumors. 32,33 Furthermore, treatment with metformin, which lowers insulin levels, decreases the incidence and size of mammary adenocarcinomas in tumor-prone transgenic mice. 34 Human glial tumors possess insulin receptors with binding activities and characteristics identical to peripheral insulin receptors, and insulin has been shown to stimulate glucose uptake in cultures of human GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, insulin binding to the IR leads to activation of IR substrate molecules and the downstream activation of the mitogen-activated protein kinase pathway. Furthermore, animal models have found that high insulin levels promote the development of aberrant crypt foci in the colon, which are posited to be colorectal cancer precursors (4), and overexpression of the IR can induce cell transformation in vitro (5). x Multivariate model plus waist circumference, insulin, free IGF-I and HT/E2.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance and hyperinsulinemia are prevalent in obese patients and insulin, in addition to its metabolic effects, has promitotic and antiapoptotic activity that may be tumorigenic. In laboratory models, for example, high insulin levels have been shown to promote the development of aberrant crypt foci in the colon (which are posited to be colorectal cancer precursors), as well as the growth of colon cancer cells (4). Furthermore, overexpression of the insulin receptor (IR) can induce cell transformation in vitro (5), and human colorectal adenocarcinomas have been shown to express the IR at high levels, indicating that these cells may be sensitive to the growth effects of insulin (6).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Grant et al (2006) demonstrated that a polymorphism in TCF7L2 is associated with increased risk of type II diabetes (T2D) [6][7][8][9][10][11][12] by impaired beta-cell function [7,9]. Epidemiologic studies have suggested that hyperinsulinemia may be related to the risk of colon adenoma and cancer [13][14][15][16]. Given its relevance to the etiology of colorectal cancer, we evaluated the association of the TCF7L2 (RS12255372) polymorphism with colorectal cancer and adenoma in the prospective Nurses' Health Study (NHS) and Health Professionals Follow-up Study (HPFS) cohorts.…”
Section: Introductionmentioning
confidence: 99%